THE INFLUENCES OF FLASH SALE PROMOTION ON SHOPPING ENJOYMENT AND IMPULSE BUYING OF SHOPEE CONSUMERS INDONESIA - Intan Nur Azizah; Indrawati Indrawati (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
In Indonesia, there is rivalry in e-commerce from not just domestic but also from a number of foreign businesses who promote their goods there. With their Flash Sale offer, Shopee Indonesia distinguishes themselves from the competition. There is no research on the characteristics of flash sales with perceived values and products involve and their implications on online shopping enjoyment and impulse buying. Research on flash sales often examines system faults and their effects on consumer purchases. This study aims to determine how flash sale aspects, such as the products they contain and the perceived values they represent, affect attitudes about them as well as how they affect consumers' enjoyment of online shopping and impulse buying. The study was conducted on flash sale users in Shopee consumers in Indonesia. On this research, data was from 275 respondents through a google form link that was spread using social media such as Whatsapp & Instagram. Data analysis is done through structural equation modelling using the Smart PLS 3 program. Based on the results, there are significant factors influencing the flash sale promotion. Product Involve and Perceived Values has a positive significant influence on Attitude toward Flash Sale. Attitude toward Flash Sale has a significant influence on Shopping Enjoyment and Impulse Buying. This research has implications for e-commerce management to maintain the characteristics of flash sale. The recommendation for further research is to research with other object with the same variables and in different times with up-to-date experts.